Preparatory Work for a World Bank Programming Mission on Civil Service Reform in Indonesia - Holfelt, Ingrid (World Bank, Washington, DC, 2013)
This report describes a mission to Indonesia, with the purpose of mapping Human Resources Management (HRM) Practices in three selected ministries: Finance (MoF), Foreign Affairs (MoFA), and Home Affairs (MoHA). The mappings within these ministries were intended to provide an input to a World Bank Programming Mission on Civil Service Reform scheduled for 2-13 February 2009 to determine what kind of support the World Bank could provide in helping the Government of Indonesia (GOI) develop its ongoing civil service reform program. This report is a summary of the information gathered and includes a comparison among the three ministries. The summary is organized in accordance with the HRM core areas: (i) human resources strategy, (ii) job classification, (iii) recruitment, (iv) career management, (v) performance management, (vi) ethics management, (vii) training and development, (viii) remuneration, and (ix) the organization of the HR divisions.